2016
DOI: 10.1007/s10854-016-5122-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in-situ oxidative preparation on electrical properties of Epoxy/PANi/MWCNTs nanocomposites

Abstract: Conductive adhesives based on Epoxy/Polyaniline/MWCNT (EPM) system doped with Paratoluensulfonic acid (p-TSA) have been successfully synthesis via different methods and characterized. The composites were prepared by in situ synthesis of aniline/MWCNTs within epoxy matrix and direct physical mixing. X-ray diffraction (XRD) spectrum established the existence of MWCNT in the structure and showed that the morphology of samples was amorphous. FT-IR results confirmed that the composites were successfully synthesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(47 reference statements)
0
3
1
Order By: Relevance
“…also reported nanocomposites with polyaniline/magnetite epoxy nanocomposites where the elongation was about 9% and, therefore, these nanocomposites are highly brittle in nature, which may be due to aggregation of the nanoparticles in the matrix. Thus, the elongation (%) was found to be far better in the present study compared to the earlier reported data . This is due to the sliding of the graphitic layers of CD and the polymeric chains of PN in the PC nanohybrid under stress, which contributes to the improvement in the elongation and flexibility of the EPCI nanocomposites .…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…also reported nanocomposites with polyaniline/magnetite epoxy nanocomposites where the elongation was about 9% and, therefore, these nanocomposites are highly brittle in nature, which may be due to aggregation of the nanoparticles in the matrix. Thus, the elongation (%) was found to be far better in the present study compared to the earlier reported data . This is due to the sliding of the graphitic layers of CD and the polymeric chains of PN in the PC nanohybrid under stress, which contributes to the improvement in the elongation and flexibility of the EPCI nanocomposites .…”
Section: Resultscontrasting
confidence: 57%
“…Thus, the elongation (%) was found to be far better in the present study compared to the earlier reported data. 27,28 This is due to the sliding of the graphitic layers of CD and the polymeric chains of PN in the PC nanohybrid under stress, which contributes to the improvement in the elongation and flexibility of the EPCI nanocomposites. 29 Moreover, the impact and scratch resistance of the nanocomposites also showed an increasing trend proportional to the dose of the nanomaterial attributed to the combined effect of aromatic aniline moieties along with the aromatic and aliphatic chains of the polymer.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…On the other hand, the increasing trend in adsorption at 2958 cm −1 [22] can be clarified with more involvement of silane coupling agents with raising the BO content. Carbonyl groups C=O are kept constant during reactions since they do not participate in the chemical fluctuations and as verified from the peak at 1731 cm −1 in all samples [23]. The fixed position of the carbonyl group results from the absence of ionic bonding between boehmite hydroxyl groups and polymer functional groups [24].…”
Section: The Effect Of Ph On the Microstructure Of Hybridsmentioning
confidence: 92%
“…However, the flexibility of these nanocomposites is very low and therefore, their applications are limited. On the other hand, Imani et al [27] prepared epoxy nanocomposites by incorporating PANi/MWCNT doped with para-toluene sulfonic acid (p-TSA). The nanocomposites showed improved electrical conductivity which is appropriately utilized for conducting adhesive application.…”
Section: Introductionmentioning
confidence: 99%